2017
DOI: 10.1016/j.jacc.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Following the Ross Procedure in Adults

Abstract: The Ross procedure was associated with excellent long-term valvular outcomes and survival, regardless of the need for reintervention. Adults presenting with aortic insufficiency or a dilated aortic annulus or ascending aorta were at greater risk for reintervention. Unlike previous reports, long-term survival was lower in Ross patients compared with matched subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 22 publications
1
80
0
5
Order By: Relevance
“…In their article in this issue of the Journal analyzing valve performance with the Ross procedure in a 22-year period, Sievers and colleagues 6 report 630 cases, with a perioperative mortality of 0.3% and a long-term survival equivalent to that of the general population. Several other institutions have reported excellent results, [7][8][9] similar to those of Sievers and colleagues, 6 and long-term results superior to those seen with mechanical valves. [7][8][9] These singleinstitution results have inspired editorials and expert opinion statements 10 advocating a significant increase in the use of the Ross procedure, particularly for young and middle-aged adults.…”
supporting
confidence: 58%
“…In their article in this issue of the Journal analyzing valve performance with the Ross procedure in a 22-year period, Sievers and colleagues 6 report 630 cases, with a perioperative mortality of 0.3% and a long-term survival equivalent to that of the general population. Several other institutions have reported excellent results, [7][8][9] similar to those of Sievers and colleagues, 6 and long-term results superior to those seen with mechanical valves. [7][8][9] These singleinstitution results have inspired editorials and expert opinion statements 10 advocating a significant increase in the use of the Ross procedure, particularly for young and middle-aged adults.…”
supporting
confidence: 58%
“…The advantages are related to the somatic growth of the cardiovascular structures and with the avoidance of anticoagulants that would be required lifelong in the case of conventional mechanical prostheses [ 14 , 15 , 16 , 17 , 18 ]. However, the incidence of pulmonary autograft (PA) expansion reported after Ross operation, without loss of integrity of the valve leaflets, varies from 20% to 40%, and reoperation is not uncommon [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the first experimental studies, the comparison between reinforced and nonreinforced pulmonary autograft took into account the variable of somatic growth that is fundamental when the Ross operation is performed during the patient’s growing age [ 35 , 36 , 39 ]. In the human series, although the rate of superior expansion of nonreinforced pulmonary transplant has been established, there is a paucity of data that report a potential clinical benefit for late outcomes over 20 years when comparing reinforced vs. nonreinforced Ross procedure [ 5 , 21 , 22 , 24 , 25 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a 25-year longitudinal study, Martin and colleagues reported 3 patients (1.0%) out of 310 who developed IE following Ross procedure. 10 Unfortunately, the time since operation was not available. India confirmed a case involving the homograft of a 54-year-old patient presenting 10 years since pulmonary autograft.…”
Section: Discussionmentioning
confidence: 99%